Contribution à la ré-évaluation de l’aire de répartition du singe à queue de soleil (Cercopithecus solatus) - Peggy Motsch; Guillaume Le Flohic; Jeremy Leclercq; Jean-Paul Gonzalez (Revue de Primatologie)
The sun-tailed monkeys (Cercopithecus solatus) is an endemic species of Gabon, where it was first observed in 1984 by Mike Harrison and described in 1988. To date, little information is available on this cryptic and rare species. To overcome the lack of studies on this species, the ECOSOL project (ECOlogy of C. SOLatus), a multidisciplinary research project, was initiated in January 2009 to improve knowledge on this poorly known species and to encourage conservation. For nearly two years, new data were acquired, in particular on the distribution area of the species. Here is the study of the southeastern limit. Thus, our study was conducted in three regions of Gabon, where the presence of C. solatus was either demonstrated (historic area), or suspected, or had never been studied before. Surveys in villages and recce walking in the field have been carried out. The results 1 / confirmed the presence of C. solatus in the historic area, 2 / seem to support the assumptions of its presence beyond the historic area, and 3 / even suggest that C. solatus would be further south-east and closer to the Republic of Congo that what was previously thought. This study contributed to reassess the distribution of populations of C. solatus within the Gabonese territory, and therefore provided additional tools to assess the conservation status of the species.